2022
DOI: 10.1111/1365-2745.13827
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific trait changes have large impacts on community functional composition but do not affect ecosystem function

Abstract: Plant functional traits can provide a mechanistic understanding of community responses to global change and of community effects on ecosystem functions. Nitrogen enrichment typically shifts trait composition by promoting the dominance of acquisitive plants (high specific leaf area [SLA] and low leaf dry matter content [LDMC]), translating into high biomass production. Changes in mean trait values can be due to shifts in species identity, relative abundances and/or intraspecific trait values. However, we do not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 77 publications
(137 reference statements)
4
21
1
Order By: Relevance
“…Meanwhile, these results also highlight the importance of intraspecific trait variations. Recent studies showed that intraspecific trait variations might be equal or greater than interspecific variations in determining community responses to biotic and abiotic environmental changes (Jessen et al, 2020;Pichon et al, 2022;Wang et al, 2022;Wilfahrt et al, 2020). Consistent with these studies, we found that the fungicide effect on plant community biomass was more related to intraspecific trait variations, rather than trait changes induced by abundance shifts (Figure 5).…”
Section: F I G U R Esupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, these results also highlight the importance of intraspecific trait variations. Recent studies showed that intraspecific trait variations might be equal or greater than interspecific variations in determining community responses to biotic and abiotic environmental changes (Jessen et al, 2020;Pichon et al, 2022;Wang et al, 2022;Wilfahrt et al, 2020). Consistent with these studies, we found that the fungicide effect on plant community biomass was more related to intraspecific trait variations, rather than trait changes induced by abundance shifts (Figure 5).…”
Section: F I G U R Esupporting
confidence: 90%
“…Due to local adaptation or phenotypic plasticity, functional traits of plant individuals within one species can vary in response to environmental changes (Albert et al, 2011;Messier et al, 2010;Violle et al, 2012). Generally, nitrogen addition can increase plant individuals' height, leaf chlorophyll content, SLA and decrease LDMC, which are related to fast growth in resource-rich conditions (Pichon et al, 2022;Wang et al, 2022;Wilfahrt et al, 2020). However, these intraspecific trait variations may increase the pathogen effect on plants because developing these fast-growing traits often comes at the cost of reduced defense against natural enemies (Coley et al, 1985;Herms & Mattson, 1992;Züst & Agrawal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that patterns of disease can be strongly influenced by inter-and intraspecific variation in SLA, but relationships between SLA and biotic interactions are being increasingly recognized as multidirectional: not only can host pace-of-life influence biotic interactions but biotic interactions can reciprocally influence intraspecific variation in host pace-of-life. For example, across 101 species embedded in alpine communities, SLA decreased with increasing herbivory [101], within eight common tundra plant species, SLA increased when mammalian herbivory was excluded [102], and across 20 species in a biodiversity manipulation, fungicide application reduced SLA within species [103]. Together with the results of this study, these experimental results highlight the potential for important feedbacks between ITV and disease risk in host communities experiencing climate change.…”
Section: Discussionsupporting
confidence: 62%
“…Studies on plant traits from the individual to the global scale have found that intraspecific and interspecific trait variation within functional groups and communities, and that between communities can strongly reflect the response of different species to limited resource competition and changes in environmental factors [3]. Interspecific variation and intraspecific trait variation are important factors affecting species coexistence and community composition [10,11].…”
Section: Introductionmentioning
confidence: 99%